2017
DOI: 10.1111/imr.12527
|View full text |Cite
|
Sign up to set email alerts
|

The CD47‐SIRPα signaling axis as an innate immune checkpoint in cancer

Abstract: Immune checkpoint inhibitors, including those targeting CTLA-4/B7 and the PD-1/PD-L1 inhibitory pathways, are now available for clinical use in cancer patients, with other interesting checkpoint inhibitors being currently in development. Most of these have the purpose to promote adaptive T cell-mediated immunity against cancer. Here, we review another checkpoint acting to potentiate the activity of innate immune cells towards cancer. This innate immune checkpoint is composed of what has become known as the 'do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
368
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 440 publications
(370 citation statements)
references
References 167 publications
1
368
1
Order By: Relevance
“…Notably, the treatment of MIT-NPs reduced Figure 6A), a membrane protein that took part in innate immune checkpoint in cancer. 32 In tumor tissue of the MIT-NPs group (2 mg/kg), a more striking number of vacuoles existed as compared with that of the control group. These vacuoles appeared in blue with AB mucin staining ( Figure 6B), indicating that acidic glycan occurs in the vacuole structure.…”
Section: Immunohistochemical Observation Of the Tumormentioning
confidence: 85%
See 2 more Smart Citations
“…Notably, the treatment of MIT-NPs reduced Figure 6A), a membrane protein that took part in innate immune checkpoint in cancer. 32 In tumor tissue of the MIT-NPs group (2 mg/kg), a more striking number of vacuoles existed as compared with that of the control group. These vacuoles appeared in blue with AB mucin staining ( Figure 6B), indicating that acidic glycan occurs in the vacuole structure.…”
Section: Immunohistochemical Observation Of the Tumormentioning
confidence: 85%
“…It plays a significant role in the innate immune checkpoint through interaction with signal regulatory protein-α (SIRPα), a myeloid inhibitory immunoreceptor. 32 A previous study had suggested that CD47 was highly expressed on primary pancreatic cancer cells and the anti-CD47 monoclonal antibodies (mAbs) could enable phagocytosis of cancer cells by macrophages as well as inhibit self-renewal of cancer stem cells. 38 In comparison to the relatively stable expression of SIRPα, the variable levels of CD47 may be relevant to immune checkpoint in cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intended/expected activity of both classes of therapeutics is to enhance phagocytic clearance of tumor cells by macrophages by inhibiting the CD47-SIRPa interaction (157), but understanding the role of CD47 in redox signaling can illuminate potential side effects of these therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic applications for cancer. The abnormal vasculature of tumors tends to be unresponsive to NO (88), but the ability of CD47 blockade to modulate responses to radiation and redox signaling involved in innate and adaptive antitumor immunity provides therapeutic opportunities for improving the activities of both conventional cytotoxic therapies and immunotherapy of cancer (134,147,157,248). Several companies are developing biologics targeting CD47 that are designed to inhibit its interactions with SIRPa, and several of these have entered human clinical trials for cancer patients (NCT02216409, NCT02678338, NCT02953509, NCT02953782, NCT02367196, NCT02488811, and NCT02641002).…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 99%